ConDAQ conductivity and temperature sensor array and data acquisition system for salt water intrusion in shore-based communities - Fajardo, Paolo Angelo R.; Valdez, Rozelle C. (2010)
Numerous coastal communities, existing in archepelagic countries like the Philippines, depend on groundwater for their daily sustenance. Groundwater can be adversely affected by saltwater intrusion and becomes brackish water, with salinity ranging from 0.5 ppt to 17 ppt, which could cause kidney ailments and death to terrestrial plants. Saltwater intrusion happens when sea water moves into inland freshwater aquifers due to the increase in the water pressure in the aquifers which may be caused by over pumping of freshwater. To monitor the extent of saltwater intrusion, periodic measurements of water salinity must be made on the shore. Sensors placed in different depths from the ground and different distances from the shoreline, can help demonstrate the extent of saltwater intrusion in the area. The aim in this project is to design a data acquisition system that can measure the salinity of water with relation to its conductivity and temperature and save the data in a memory device. This system will aid geologists in their field tests: providing an easy and non-obtrusive way of acquiring data and a cheaper alternative to commercial sensors.
Thesis (B.S. Electronics and Communications Engineering) -- University of the Philippines, Diliman
Keywords: Automatic data collection systems; Saltwater encroachment -- Monitoring; Signal processing -- Digital techniques; Sensor networks -- Data processing; ConDAQ